2008
DOI: 10.1148/radiol.2463062071
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Bridging: Depiction Rate and Morphology at CT Coronary Angiography—Comparison with Conventional Coronary Angiography

Abstract: The depiction rate of MB is greater with 64-section CT coronary angiography than with conventional coronary angiography. The degree of systolic compression of MB significantly correlates with tunneled segment depth but not length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
1
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 25 publications
8
89
1
5
Order By: Relevance
“…Myocardial bridging is defined as a segment of a major epicardial coronary artery running intramurally through the myocardium beneath a muscle bridge [64]. Although myocardial bridging is considered as a common, benign condition, complications, including transient ischemia and sudden death, have been repetitively described in the literature [65].…”
Section: Acute Aortic Dissectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myocardial bridging is defined as a segment of a major epicardial coronary artery running intramurally through the myocardium beneath a muscle bridge [64]. Although myocardial bridging is considered as a common, benign condition, complications, including transient ischemia and sudden death, have been repetitively described in the literature [65].…”
Section: Acute Aortic Dissectionmentioning
confidence: 99%
“…One of the most recent CT types, dual-source CT (DSCT), maintains the high spatial resolution of previous single-source 64-slice CT systems while enabling ECGgated imaging with an increased temporal resolution [13]. A number of studies have shown robust and auspicious results of DSCT coronary angiography regarding image quality [14,15] and accuracy [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is neither reasonable nor practical to use such an invasive imaging modality merely to quantify MB compression in patients without coronary artery disease. Coronary CTA has been proven to be more sensitive than ICA for detection of MB due to its ability to visualize the intra-mural course of coronary arteries [12][13][14][15][16]. However, determination of compression extent requires artifact-free images of end-systolic phases, which are sometimes not available with low-dose prospective acquisition [12].…”
Section: Discussionmentioning
confidence: 99%
“…MB lesions were divided into three subgroups according to the extent of systolic compression as determined by end-systolic phases of CTA imThe MB detection rate varies significantly between the different imaging modalities of coronary computed tomography angiography (CTA) and invasive coronary angiography (ICA). Coronary CTA usually reveals a much higher incidence of MB than ICA [12][13][14][15][16] due to the capability of coronary CTA to detect MB without the presence of systolic compression. The clinical significance of myocardial bridging lies in related regional hemodynamic changes caused by dynamic compression.…”
Section: Cta Image Reconstruction and Analysismentioning
confidence: 99%
See 1 more Smart Citation